THE APPLICATION OF EGP MATERIALS TO ATC STUDENTS OF CASEA MAKASSAR - Agus Rahmat; Muawwal Al As'ary (UIN Raden Mas Said Surakarta, 2017)
The objectives of this research were to find out the application of English for Generic Purposes (EGP) materials to the Air Traffic Controller (ATC) class in learning English at Civil Aviation Safety and Engineering Academy (CASEA), Makassar and the studentsâ€™ perceptions toward the application the materials. This research employed descriptive qualitative research design. It applied cluster random sampling technique. The informants of this research were nineteen that consist of one lecturer and 18 ATC students of CASEA Makassar. The data were collected by observations and interviews. The observations were conducted to gather the data about the application of the materials to the students while the interviews were done to support and strengthen the data from observations whereas the interviews were also purposed for analyzing the studentsâ€™ perception toward the application of the materials. The result of this research showed that (1) the application of EGP materials to ATC students of CASEA Makassar was quite effective since the lecturer had various ways in teaching English and could teach the students based on their needs as aviation studentsÂ and (2) most of the students felt that both ESP (English for Specific Purposes) and EGP were so beneficial for them since as aviation cadets, they are required to be able to communicate in English. Despite the necessities for learning EGP and ESP, most of the students contended that ESP was more essential in their working environments as aircraft controllers.